Simulation and experimental verification of the precision finishing method for optical free-form surface segmentation - Chenhua Jiang; Enzhong Zhang; Wei Zhang; Jiaqi Hu; Jiechen Guo; Xiaodong Li (PLoS ONE, 2025)
Optical free-form surfaces are often used to manufacture optical components such as lenses and mirrors, and free zone surface optical components are widely used in aerospace optics. To address the issues of low processing quality and overall efficiency in the machining of aluminum alloy free-form surfaces, an efficient numerical control machining method based on surface segmentation has been proposed. The segmentation of free-form surfaces is divided into two stages: the recognition of surface partitions and the determination of surface boundaries. Initially, the free-form surface is roughly classified into three types of regions: convex (planar), concave, and saddle-shaped, based on its curvature characteristics. The surface is then further segmented using the fuzzy c-means clustering algorithm. Subsequently, the Voronoi diagram algorithm is employed to construct the boundaries of the free-form surface ultimately. In a UG simulation, the segmentation machining method was compared with the conventional overall machining method, demonstrating a reduction in the machining path by 12.18% and machining time by 13.92%. Finally, experiments revealed a 12.28% reduction in machining path length and a 12.56% reduction in machining time using the segmentation machining method. This verifies the practicality of the free-form surface segmentation approach and proves that it can effectively enhance machining efficiency and quality.